Need Analysis : the ICT and Gender Issues - Nwanesi, Peter Karubi; Goy, Siew Ching (International Organization of Scientific Research (IOSR, 2015)
The fact remains that the increase and diversification of the information and communications technologies, have continued to usher in a new era in human development. Often mainstream views depict that such technologies have only technical rather than social implications. Their position is based on the notion that the remarkable affirmative transformations introduced by these ICT technologies have not touched all levels of societies. To some extent such views are accurate. This may be attributed to the fact that the existing power relations and structures in societies often determine the levels of benefits groups or classes in a given society enjoys. In view of this, we argue that ICT’s projects or technologies are often not gender neutral. The vital questions as suggested by Gurumurthy are; Who benefits from ICTs? Who is dictating the course of ICTs? Is it possible to harness ICTs to serve the larger goals of equality and justice? And is there any hidden costs in terms of human development should such technology be made available without gender equality? Is it compulsory for any research on ‘need analysis on ICT’ to pay a special attention to gender issues in a given community? The last question provoked much interest in this study and it is the cornerstone of this paper. Indeed, the above views made it unavoidable necessary to critically examine ICT and gender issues in relation to the Orang Asil of West Malaysia. In addition, this article explores ICTs and gender relations in giving voices to Orang Asli women.